Characterization of reciprocity gaps from interference tests in fractured media through a dual porosity model. Issue 3 (6th March 2016) - Sanchez‐Vila, X.; Ackerer, P.; Delay, F.; Guadagnini, A.
Abstract: We analyze drawdown reciprocity gaps emerging in interference tests performed in a confined fissured karstic formation. Modeling the system as a dual porosity continuum allows characterizing the dynamics of the relative contribution of the connected fractures and the rock matrix to the total flow rate extracted at the pumping wells. Observed lack of reciprocity of drawdowns can then be linked to the occurrence of processes that are not accounted for in the classical flow models based on a single‐continuum representation of the system through flow equations grounded on Darcy's law only. We show that interpreting the system as a dual porosity continuum can cause drawdown reciprocity gaps to emerge as a consequence of local effects associated with an identifiable contribution of the matrix to the total fluid extracted at the well location during pumping. These theoretical results are then employed to identify the contribution to the flow being supplied to the pumping well by the low conductivity matrix constituting the host rock formation, in contrast to that provided by the fractures. An application to data from two interference tests performed at the Hydrogeological Experimental Site (HES) in Poitiers, France, illustrates the approach. We show that, whenever the matrix is assumed to provide a contribution to the total flow rate extracted, nonreciprocity is expected, the latter being linked to the occurrence of a differential drawdown between fracture and matrix at the pumping well. This difference decreases with time in the example presented, displaying a power law late time behavior, with nonreciprocity effects persisting up to remarkably long times. Key Points: Reciprocity gaps of drawdowns can arise in interference tests in fractured media Reciprocity gaps emerge mathematically depending on the way the pumping well is embedded in the model Nonreciprocity informs on dynamics of fracture/matrix contribution to pumping rates